The Impact of Air Pollution on Consumer Spending - Kim, Sanghwa; Trusov, Michael (Journal of Marketing, 2025)
Air pollution is a growing threat to economies and societies. Despite the common knowledge that air pollution impairs emotions and cognition and, hence, behavioral outcomes, the impact of air pollution on consumer spending remains an open question. Analyzing air quality readings and individual-level credit card transactions in South Korea, this article shows that consumers spend more money when air quality is poorer. This correlation is more prominent in hedonic categories, such as entertainment or leisure activities, where the nature of consumption is characterized by greater emotional benefits. The authors consider potential explanations, and the leading hypothesis is that consumers treat spending as a mood-regulating resource. The results survive an array of robustness checks and are supported in a controlled experiment, reinforcing a causal inference behind the main findings. The authors provide implications for stakeholders to develop a sustainable marketing program that not only pursues managerial interests but also concerns consumer well-being in the face of environmental change.